THE EFFECT OF TRANSACTIONAL LEADERSHIP ON EMPLOYEES' PRODUCTIVITY: EXPLORATORY STUDY; DUHOK - ALABDULLAH, AHMED ABDI FAQI (Fırat Üniveristesi, 2021)
Bu araştırmanın temel amacı işlemsel liderliğin çalışanların üretkenliği üzerindeki etkisini ölçmektir. Bu amaçla Duhok ilindeki özel sektör çalışanları örneklem olarak seçilmiştir. Pek çok işletme özellikle COVİD 19 ile birlikte iş ve çevresel bir dönüşüm yaşamaktadır. Özellikle bu dönemlerde liderlik tarzlarının organizasyonlar ve çalışan üretkenliği üzerindeki etkisini anlamak oldukça önem kazanmaktadır. Bu nedenle araştırma seçilen şirketlerin lider yöneticilerine yoğunlaşmaktadır. Araştırmada 120 anket dağıtılmış ve analize uygun sağlıklı 98 anket elde edilmiştir. Anketlerin yanıtlanma oranı %87,5'tir. İşlemsel liderliğin çalışanların üretkenliği üzerindeki etkisini analiz edebilmek için her iki değişken ve alt boyutları arasında hipotezler geliştirilmiş ve hipotezleri test etmek için standart sapma, korelasyon, regresyon gibi bir dizi istatistiki yöntem ile analiz yapılmıştır. Araştırma sonuçları işlemsel liderlik ile çalışan üretkenliği arasında istatistiki olarak anlamlı ve pozitif bir ilişki olduğunu göstermektedir. Bir başka ifade ile yöneticiler işlemsel liderlik yaklaşımını benimsediklerinde çalışanların üretkenliği artış göstermektedir. İşletmelerde koşullu ödül ve ceza sistemlerinin kurulmasının işletmelerin üretkenliğine katkı sağlayacağı da önemli bulgulardan biridir. Araştırmanın son bölümünde bulgularından yola çıkarak organizasyonlara büyüme ve sürdürülebilir rekabet avantajı elde edebilmeleri için işlemsel liderliğe ve üretkenliğe odaklanan bir dizi öneri sunulmaktadır.

We study how transactional leadership affects the employee's productivity in a number of companies in Duhok city. Due to the transformation of the business environmental, especially after COVID 19, it is important to understand how such leadership styles affect the organization's and employees' productivity. The participants within this study consisted of managerial leaders in the selected companies. There were a total of (120) questionnaires mailed out and (98) usable questionnaires were returned, yielding (87.5%) of percent response rate. Hence, by using hypotheses to evaluate a correlation that discovers the relationship between both variables of the study, the effect of transactional leadership on the employees' productivity and its dimensions. The study analysed the data to provide answer in the research sample, and hypothesis testing using a number of methods and statistical tools such as standard deviation, correlation, and regression and one-way ANOVA that was verified by the premise of research. The study found that there is a significant and positive correlation between transactional leadership and employees' productivity, this means that the more responsive managerial leaders are to depend on transactional leadership in their activities then this will lead to an increase in the level of productivity and organizational growth. An important conclusion is that the transactional leadership has positively contributed to an increase in employees' productivity in the companies of the study sample. Given these finding, we suggest that companies and managerial leaders actively increase their leadership abilities and enter the business competition in the market place. Moreover, the study found that state there are differences in transactional leadership and employee's productivity according to demographic characteristics except academic achievement differences. Furthermore, a set of recommendations are highlighted that mainly focus on the transactional leadership and the productivity of employees to sustain the organization growth and success.
İşlemsel liderliğin çalışanların verimliliği üzerindeki etkisi: Açıklayıcı bir araştırma; Duhok
Keywords: İşletme